"I didn't feel like I could trust her and that felt really risky": a phenomenographic exploration of how Australian Midwives describe intrapartum risk. (March 2023) - Gabriel, Laura; Reed, Rachel; Broadbent, Marc; Hastie, Carolyn
Abstract: Objective: Concepts of intrapartum risk are not well explored in the Australian context. In response to an increasing focus on risk in maternity care, we sought to obtain insight into what Australian midwives conceptualised as intrapartum risk. Design: The research was conducted using a phenomenographic approach. Following ethical approval, in-depth semi-structured interviews were used to determine the qualitatively different ways midwives conceptualise intrapartum risk. Setting: This project was undertaken across different midwifery practice settings in Australia. Participants: Australian midwives (n=14) with expertise in caring for women in the intrapartum period volunteered to participate in the study. Findings: When discussing their experience of intrapartum risk, midwives focused on the external horizon of the woman as the risk, that included the internal horizons of being labelled as clinically high risk, working relationships within transdisciplinary risk and institutional risk . Risks were orientated toward the woman as well as to the midwives. Key conclusions: The midwives in this study conceptualised that intrapartum risk was associated with the woman including being labelled as high risk in addition to certain challenges within the midwife-woman relationship, particularly if there was a lack of reciprocal trust. Implications for practice: This study supports current evidence that improved collaborative professional relationships are integral to safety in maternity care. It reinforces continuity of midwifery care as important, and particularly as a way of mitigating intrapartum risk. Further research is required to inform what challenges experienced in the midwife-woman relationship contribute to concepts of risk.